Espaciar Armar Compactar - Otárola-Mora, Mauricio (Instituto Tecnológico de Costa Rica., 2017)
The present project focuses on the small scale as an approach for the reconfiguration and intervention of the existing infrastructure of the Community Center Building of Jesus, Santa Bárbara, Heredia through “spacing”, assembling and compacting operations. The general objective of the proposal is to increase the occupation and articulation of the existing infrastructure through specific operations, in this sense, the small scale is understood as a tool for the realization of an architectural solution closer to the economic and management constraints that exist in the context. The design arises from the architectural inquiry about the 3 spatial operations (“spacing”, assembling and compacting) which function systemically in the new community space. When carrying out a theoretical research parallel to the practical proposal, the process is opened beyond the solution of the design and towards reflection, discussion and writing around the way in which architecture is approached. In this way, the ultimate goal of this project is not in the design for the community center itself, but in the questioning of architectural themes that are commonly left out of academic processes such as: the importance of small scale, architectural research as a form of knowledge and the concept of objectbuilding as the only manifestation of the architectural process.
Proyecto de reconfiguración e intervención de la infraestructura del Centro Comunitario de Jesús de Santa Bárbara de Heredia
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, 2017
Keywords: Centros comunitarios; Proyectos arquitectónicos; Arquitectura